CESifo World Economic Survey February 2004 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2004)
World Economic Climate: World Economic Climate considerably improved - Economic Expectations: Economic expectations for the next six months are highly optimistic - Inflation: Inflation will remain moderate - Interest Rates: Begin of tightening cycle expected - Currencies: Growing overvaluation of the euro - Special Topic: Fear of terrorism has affected business prospects for 2004 in several regions
Keywords: 330